Guest Satisfaction to Stay in The Four-Star Rating Hotel in Padang: The Influence Of Hospitableness and Guest Engagement - Arifandi Ilham; Wanda Melisa Nurlita; Wira Tri Annisa; Feri Ferdian (Nawasena: Jurnal Ilmiah Pariwisata, 2023)
The purpose of this research is to find out how the hospitableness and guest engagement that exists between employees and guests have an impact on guest satisfaction. This type of research is a quantitative descriptive research with a causal associative method. The population in this study were all guests who had stayed at a four-star hotel in the city of Padang. The sampling technique is non-probability sampling using purposive sampling. The number of samples in this study amounted to 97 responses. Data collection techniques were carried out using a questionnaire with a Likert scale that had been tested for validity and reliability. The data analysis used in this research is descriptive analysis with the help of SPSS version 20.00. From the results of the research that has been done, the Friendliness and Guest Involvement variables have a positive and significant effect on guest satisfaction at four-star hotels in the city of Padang. It can be said that based on this research, guest satisfaction can occur if the hotel can provide hospitableness and guest engagement good relations with guests during their stay, then guests will feel satisfied.